Robotic Approach to Ureteral Endometriosis: Surgical Features and Perioperative Outcomes - Giannini, Andrea; Pisaneschi, Silvia; Malacarne, Elisa; Cela, Vito; Melfi, Franca; Perutelli, Alessandra; Simoncini, Tommaso (Frontiers in Surgery, 2018)
Introduction: Surgical treatment of ureteral endometriosis is necessary to relieve urinary symptoms of obstruction and to preserve renal function. Which surgical approach to ureteral endometriosis should be considered the most appropriate is debated, due to the lack of scientific evidence. The aim of the present study is to assess the feasibility and to describe the perioperative outcomes of minimally invasive treatment of deep ureteral endometriosis using robotic assistance, highlighting the technical benefits and the limits of this approach. Method: A case-series including 31 consecutive patients affected by high-stage endometriosis including ureteral endometriosis using robotic assistance in our Department between November 2011 and September 2017. Results: All procedures were successfully completed by robotic technique, resulting in full excision of the parametrial nodules involving the ureter. Mean operating time was 184.8 ± 81 min. Mean hospital stay was 4.02 ± 3 days. Perioperative complications occurred in five patients and 4 out of 5 involved the urinary tract. Conclusions: Robotic surgery for deep infiltrating endometriosis of the ureter was feasible and allowed complete resection of ureteral nodules in all cases. No intraoperative complications arose, but a non-negligible rate of urinary tract complications was detected. This calls for a careful assessment of the benefits and specific risks associated with the use of robotic surgery for the treatment of deep infiltrating endometriosis of the ureter.